The ionic liquid-assisted sample preparation method pTRUST allows sensitive proteome characterization of a variety of bacterial endospores to aid in the search for protein biomarkers - Masato Taoka; Ritsuko Kuwana; Yoshinari Murakami; Akiko Kashima; Yuko Nobe; Takamasa Uekita; Hiromu Takamatsu; Tohru Ichimura (PLoS ONE, 2025)
Bacterial endospores are ubiquitous and are responsible for various human infections. Recently, we reported that an ionic liquid (IL)-based sample preparation method (named pTRUST) facilitated highly efficient shotgun analysis of the Bacillus subtilis spore proteome in trace samples. In this study, we evaluated the efficiency and applicability of the pTRUST technology using three different spore preparations: one purified from the closely related subspecies B. subtilis natto and two from B. licheniformis and B. cereus. We showed that the pTRUST method allowed rapid solubilization and processing of all tested spore samples prepared for highly sensitive mass spectrometry (MS) analysis. Bioinformatics analysis using the BLAST program suggested that a set of 25 proteins commonly identified between the above three species and B. subtilis spores may be universal biomarkers among various bacterial species, including 43 spore-producing bacteria associated with industrial dairy processing environments and product spoilage. In contrast, the two identified proteins, D4FV94 in B. subtilis natto and Q737A2 in B. cereus, are likely species-specific biomarkers, because their orthologs are absent or rare in all organisms. The sensitivity and applicability of pTRUST, along with the putative protein biomarkers identified in this study, will facilitate a wide spectrum of spore research for biological and clinical applications.